Risk of osteoporosis in patients treated with direct oral anticoagulants vs. warfarin: an analysis of observational studies - Liu, Yumeng; Xie, Xiaoping; Bi, Songqi; Zhang, Qiong; Song, Qingxu; Sun, Yang; Yu, Tiecheng (Frontiers in Endocrinology, 2023)
Aims Evidence on the association between the risk of new-onset osteoporosis and oral anticoagulants remains controversial. We aimed to compare the risk of osteoporosis associated with the use of direct oral anticoagulants (DOACs) with that associated with warfarin use. Methods Studies published up to 15 March 2023 that investigated the association between the use of DOACs and warfarin and the incidence of osteoporosis were identified by online searches in PubMed, Embase, the Cochrane Library, and Web of Science conducted by two independent investigators. Random-effects or fixed-effect models were employed to synthesize hazard ratios (HRs)/relative ratios (RRs) with 95% confidence intervals (CIs) for estimating the risk of osteoporosis correlated with DOAC and warfarin prescriptions (PROSPERO No. CRD42023401199). Results Our meta-analysis ultimately included four studies involving 74,338 patients. The results suggested that DOAC use was associated with a significantly lower incidence of new-onset osteoporosis than warfarin use (pooled HR: 0.71, 95% CI: 0.57 to 0.88, p < 0.001, I2: 85.1%). Subanalyses revealed that rivaroxaban was associated with a lower risk of osteoporosis than both warfarin and dabigatran. In addition, DOACs were associated with a lower risk of developing osteoporosis than warfarin in both male and female patients, in patients with atrial fibrillation (AF), and in patients who underwent therapy for > 365 days. Conclusion DOAC users experienced a lower incidence of osteoporosis than warfarin users. This study may give us insight into safe anticoagulation strategies for patients who are at high risk of developing osteoporosis. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42023401199.